Magnetic field distribution simulation and performance experiment of a magnetic seed-metering device based on the combined magnetic system - Liu, Wei; Hu, Jianping; Yao, Mengjiao; Zhao, Jun; Lakhiar, Imran Ali; Lu, Chuantong; Pan, Haoran; Wang, Wei (International Journal of Agricultural and Biological Engineering, 2021)
The magnetic seed-metering method is one of the universal approaches for plug tray seeding. Conventional electromagnetic and permanent-magnetic seed-metering devices either cannot supply a desirable magnitude of magnetic force or need a seed-clearing mechanism. Thus the objective of this research was to develop a combined magnetic system (CMS) seed-metering device for generating higher magnetic forces than the electromagnetic ones without using any auxiliary seed-clearing mechanisms. Firstly, the CMS component was designed and its magnetic field distributions in both attractive and clearing states were obtained by finite element method simulations. Secondly, based on the CMS components, a magnetic seed-metering device was developed and validated by a prototype experiment. The simulation results displayed that along the axial direction of the magnetic head, the maximum magnetic flux density in the clearing state was 21.03% of that in the attractive state. In addition, along the radial direction, the proportion was 24.16%. Concerning the spatial magnetic flux density distribution, the magnetic flux density on the seeding planes of CMS components (approximately 60 mT) was higher than that of transitional space between two CMS components (nearly 0 mT). As for the seeding performance experiment, when the rotational speed of the roller was 21 r/min and the exciting current was 0.15 A, the highest single rate was acquired (90.20%). In the same condition, the reseeding rate was 5.88% and the miss-seeding rate was 3.92%. The results suggest that the magnetic field distribution and seeding performance of the developed magnetic seed-metering device are acceptable. Therefore, the developed magnetic seed-metering device can be used in practical plug tray seeding processes.Keywords: seed-metering device, magnetic field, magnetic flux density, finite element method, simulationDOI: 10.25165/j.ijabe.20211401.5852Citation: Liu W, Hu J P, Yao M J, Zhao J, Lakhiar I A, Lu C T, et al. Magnetic field distribution simulation and performance experiment of a magnetic seed-metering device based on the combined magnetic system. Int J Agric & Biol Eng, 2021; 14(1): 108–117.